PELATIHAN PENGELOLAAN KEUANGAN BAGI KOMUNITAS IBU-IBU RUMAH TANGGA MANDIRI KELOMPOK UKM ASMARANDHANA - Tri Rinawati; Yohanes Suhardjo; Edy Suryawardana; Sugeng Rianto (JURNAL ABDIMAS PLJ, 2022)
Independent housewives need financial support who are members of a group of inclusive economic and financial development programs under the name Asmarandhana under the guidance of Rorokenes. Its administrative activities are located at Jalan Bukit Putri No.17 Bukit Sari Semarang. Some of these mothers have children with special needs, so they have difficulty if they have to work outside the home leaving their children. Most of the mothers run businesses on a small scale with various types of businesses, which are used to fulfill their daily needs. Most of the members of the Asmarandhana group in their business practices have not implemented good financial management. In financial management there is no separation between business finances and family finances so that income does not reflect business profits and cannot describe the condition of business profits and losses. The purpose of service activities is to provide better knowledge, understanding and skills for Asmarandhana group members in managing business finances in improving family welfare   and   forming   target   community   members   into   productive   and   beneficial communities for the surrounding community. The form of this service activity is to provide business  financial  management  training,  namely how  to  manage transactions,  how  to prepare financial reports including income statements, capital changes reports, balance sheets and cash flow reports. The service activity was held on Saturday, June 4, 2022 at the Soto Pandanaran Hall on the 2nd (second) floor. This activity is carried out for 1 (one) day from 10.00 to 13.00 (1 x 3 hours). Service activities are carried out through the stages of Focus Group Discussion (FGD), lectures, discussions and questions and answers. The service participants were very enthusiastic in participating in the training activities. The service  participants  felt  very  helped  by  the  training  activities  in  managing  business finances.  The training participants  thought that  recording  transactions and  preparing reports were simpler, shorter and more practical and easier to understand.Keywords: Independent Housewives, Rorokenes, Finance